2017
DOI: 10.20950/1678-2305.2017v43n3p322
|View full text |Cite
|
Sign up to set email alerts
|

Fatores antinutricionais da soja crua no crescimento e respostas hematológicas da tilápia do nilo

Abstract: RESUMOO objetivo do estudo foi avaliar o efeito dietético dos fatores antinutricionais da SC (soja crua) na hematologia e no desempenho produtivo da tilápia-do-nilo (Oreochromis niloticus). Foi realizada a substituição de 0,0; 15,0; 25,0 e 35,0% da proteína do farelo de soja (FS) pela proteína da SC. Neste estudo, foram avaliados o efeito da substituição do FS por SC no perfil hematológico e desempenho produtivo da tilápia após 90 dias experimentais. Foi avaliado a atividade ureática da SC, indicando a presenç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…In the present study, stress caused by molasses application rates of 50% (C/N 20:1) of total daily feed (BFT-50 and BFT-C50) caused significant changes in the hematocrit level and the erythrocyte counts of the fish, resulting in macrocytic anemia. The values found in the treatments with molasses application rates of 30% of total daily feed (C:N 12:1) (BFT-30 and BFT-C30) remained in the ideal range described by several authors (20 to 32% for hematocrit and 1.9 to 5.0 x 10 6 µL -1 for erythrocyte counts) (Ueda et al, 1997;Signor et al, 2010;Costa et al, 2014;Martins et al, 2017). However, the values for treatments molasses application rates of 50% of total daily feed (BFT-50 and BFT-C50) were below the recommended level (21-44% hematocrit level and 1.50 to 3.76 x 10 6 µL -1 erythrocyte count) (Tavares-Dias, 2015).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In the present study, stress caused by molasses application rates of 50% (C/N 20:1) of total daily feed (BFT-50 and BFT-C50) caused significant changes in the hematocrit level and the erythrocyte counts of the fish, resulting in macrocytic anemia. The values found in the treatments with molasses application rates of 30% of total daily feed (C:N 12:1) (BFT-30 and BFT-C30) remained in the ideal range described by several authors (20 to 32% for hematocrit and 1.9 to 5.0 x 10 6 µL -1 for erythrocyte counts) (Ueda et al, 1997;Signor et al, 2010;Costa et al, 2014;Martins et al, 2017). However, the values for treatments molasses application rates of 50% of total daily feed (BFT-50 and BFT-C50) were below the recommended level (21-44% hematocrit level and 1.50 to 3.76 x 10 6 µL -1 erythrocyte count) (Tavares-Dias, 2015).…”
Section: Discussionmentioning
confidence: 51%
“…A good indicator of fish health may be hematological indices (Martins et al, 2017). In the present study, stress caused by molasses application rates of 50% (C/N 20:1) of total daily feed (BFT-50 and BFT-C50) caused significant changes in the hematocrit level and the erythrocyte counts of the fish, resulting in macrocytic anemia.…”
Section: Discussionmentioning
confidence: 58%
“…For instance, soybean, which is characterized by high protein percentage, appealing smell, low price [ 52 ], and low content of specific anti-nutrients, including oligosaccharides and allergic proteins [ 53 ]. However, the growth of O. nana in the present study with soybean had the lowest rate compared with other tested diets, which could be due to the high concentration of soybean meal, or nitrogen wastes and induced toxicity [ 54 ]. In the study of El-khodary et al [ 27 ] who found that Cyclops fed on soybean had high density (27 individuals mL −1 ) but this diet provided low nutritional value compared with those fed on microalgae.…”
Section: Discussionmentioning
confidence: 93%
“…The 58% boiled FFSB treatment group also had the highest body lipid content. In a different study, replacing soya bean meal protein with raw soya beans in tilapia diets at levels of 15%, 25% and 35% affected the weight gain, feed intake and protein retention (Martins et al, 2017). HSI and whole‐body lipid content were lowest in the 35% group in addition to fish having a significantly higher plasma neutrophil count.…”
Section: Discussionmentioning
confidence: 99%